A study on community older people’s willingness to use smart home—an extended technology acceptance model with intergenerational relationships - Wei, Wenjing; Gong, Xiaodong; Li, Jian; Tian, Kun; Xing, Kai (Frontiers in Public Health, 2023)
Smart home services can promote a sustainable lifestyle for seniors, despite their low adoption rate of these services. This study aimed to determine if intergenerational support models could influence the acceptance of smart home services among older adults. We conducted an online survey of 298 older adults in China and applied Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the effect of 10 hypothesized predictor variables. Our findings indicated that intergenerational relationships significantly predict the use of smart home services by the elderly. Specifically, intergenerational instrumental support has a direct effect on behavioral intention to use smart homes. Moreover, intergenerational emotional and financial support have indirect effects on life satisfaction, which in turn affects behavioral intention. This study provides practical implications for in-home aging senior citizens seeking to adopt smart home services.